Tobacco Taxation Incidence : Evidence from the Russian Federation - Fuchs, Alan; Matytsin, Mikhail; Obukhova, Olga (World Bank, Washington, DC, 2018)
Despite the well-known positive effects of tobacco taxes on health outcomes, policy makers avoid relying on such taxes because of their possible regressive impact. Using an extended cost-benefit analysis to estimate the distributional effect of cigarettes in the Russian Federation, this paper finds that the long-run impact may in fact be progressive. The methodology applied incorporates the negative price effect caused by an increase in tobacco taxes, combined with a presumed future reduction in medical expenditures and a rise in working years caused by a reduction in the rate of smoking among the population. The analysis includes estimates of the distributional impacts of price rises on cigarettes under various scenarios, based on information taken from the Russia Longitudinal Monitoring Survey -- Higher School of Economics for 2010–16. One contribution is the quantification of impacts by allowing price elasticities to vary across consumption deciles. Overall, cigarette taxes exert a positive long-term effect on household incomes, although the magnitude depends on the structure of the conditional price elasticity. If the population is more responsive to tobacco price changes, then it would experience greater gains from the health and extended work-life benefits.